How Canva Aplication Used by Pre-Service Teacher: A Study at PPG Students in Indonesia - Muhsin, Muh Arief (Jurnal Riset dan Inovasi Pembelajaran, 2024)
This qualitative study looks at the use of Canva as a learning media tool among pre-service teachers enrolled in the Professional Teacher Education Program (PPG). Data were collected through on-the-ground interviews with four PPG students to better understand their experiences and perceptions of using Canva to create teaching materials. The study investigated the most common forms of teaching materials created with Canva, desired features, key benefits, and constraints faced by the teachers. Findings showed that pre-service teachers generally had positive experiences using Canva, praising its ease of use, time-saving capabilities, and collaboration features. They commonly develop presentation materials, infographics and posters using Canva's vast library of templates and graphic tools. Its main advantages include increased teaching efficiency and the creation of visually appealing content that promotes student engagement and understanding. However, issues such as limited internet connectivity and restrictions on Canva's free features underscore the need for improved infrastructure and institutional assistance. This study highlights Canva's potential to improve educational practices and offers significant insights for building curricula and strategies for technology integration in education.